First, break each force into its x and y components.
F1 = 33 lb → F1x = 33 lb (cos 47º) F1y = 74 lb (sin 47º)
F2 = 74 lb → F2x = - 74 lb (cos 48º) F2y = 74 lb (sin 48º)
(48º is the reference angle for 132º in the second quadrant. In the second quadrant, x is negative and y is positive so the x force is negative and the y force is positive.)
Then, find the sum of the x components and the sum of the y components.
ΣFx = F1x + F2x = 33 lb (cos 47º) - 74 lb (cos 48º) = -27.01 lb
ΣFy = F1y + F2y = 33 lb (sin 47º) + 74 lb (sin 48º) = 79.13 lb
Finally, find the magnitude of the resultant force by taking the square root of the x components squared plus the y components squared.
Fresultant = √[(ΣFx)2 + (ΣFy)2] = √[(-27.01 lb)2 + (79.13 lb)2] = 83.61 lb